Maritime political risk conceptualisation and mapping of maritime political risk in order to improve management and mitigation strategies for the offshore oil and gas industry in the Gulf of Guinea - Johansen, Johan (Stellenbosch : Stellenbosch University, 2011)
Thesis (MA )--Stellenbosch University, 2011.